A Nation of Informants: Reining In Post-9/11 Coercion of Intelligence Informants - Shamas, Diala (2018)
This article challenges the adequacy of the existing legal and regulatory framework governing informant recruitment and coercion practices to protect fundamental rights, informed by the Muslim-American experience. It looks at the growing law enforcement practice of recruiting informants among Muslim-American communities for intelligence gathering purposes. Although the coercion of law-abiding individuals to provide information to federal law enforcement agencies for intelligence gathering purposes implicates significant rights, it is left unregulated. Existing, albeit limited, restraints on the government agents’ ability to coerce individuals to provide information either assume a criminal context, or are driven by historical concerns over FBI corruption. As the U.S. government engages in widespread surveillance of Muslim-American communities, it relies heavily on recruiting members of those communities as informants. These individuals are targeted for their community ties, or their religious or linguistic knowledge—and not because of any nexus they might have to criminal activity. This has led FBI agents to search for coercive levers outside of the criminal process and that have far fewer procedural protections—namely, immigration and watch-listing authorities. Thus, existing protections that have evolved to prevent civil rights violations in the criminal informant context—limited as those protections may be—do not apply. In light of these expanding authorities and the significant rights at stake, this article makes several proposals that would regulate the recruitment of intelligence informants